2017
DOI: 10.1016/j.apcatb.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Exsolution of Re-alloy catalysts with enhanced stability for methane dry reforming

Abstract: The valorization of natural gas is a highly important process which could enable the production of hydrogen or clean synthetic fuels. Methane reforming with carbon dioxide provides an environmentally friendly route for methane conversion to synthesis gas while consuming two greenhouse gasses. Large-scale implementation of this process has been stalled by the lack of stable catalysts owing to variety of deactivation mechanisms such as carbon accumulation (coking) and sintering. We created doped perovskite precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 50 publications
1
51
0
1
Order By: Relevance
“…Zubenko et al examined Ni and Re loaded on a LaFeO 3 perovskite precursor via solid‐phase crystallization for CO 2 reforming of CH 4 . The excellent activity and stability was attributed to the presence of Re‐alloy nanoparticles (Ni‐Fe, Re‐Fe, and Re‐Ni‐Fe) as consequences from the exsolution process of the perocskite precursor.…”
Section: Dry Reforming Of Methane Over Bimetallic Ni‐noble Metal‐basementioning
confidence: 99%
See 1 more Smart Citation
“…Zubenko et al examined Ni and Re loaded on a LaFeO 3 perovskite precursor via solid‐phase crystallization for CO 2 reforming of CH 4 . The excellent activity and stability was attributed to the presence of Re‐alloy nanoparticles (Ni‐Fe, Re‐Fe, and Re‐Ni‐Fe) as consequences from the exsolution process of the perocskite precursor.…”
Section: Dry Reforming Of Methane Over Bimetallic Ni‐noble Metal‐basementioning
confidence: 99%
“…Wysocka et al [15] [16]. The excellent activity and stability was attributed to the presence of Re-alloy nanoparticles (Ni-Fe, Re-Fe, and Re-Ni-Fe) as consequences from the exsolution process of the perocskite precursor.…”
Section: Introductionmentioning
confidence: 99%
“…The DRM has been previously investigated on many catalysts based on noble and transition metal elements. Although noble-metal catalysts are active and less sensitive to carbon accumulation, Ni-based catalysts are preferred due to their ability to activate the C-H bond, relatively low cost, and availability [6][7][8][9]. It is well known though that Ni-based catalysts suffer from deactivation during DRM largely owing to coking and sintering [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mesoporous silica and alumina has been received much attention as supports of Ni nanoparticles since Ni nanoparticles that are embedded in pores of those supports can exhibit good sintering resistance at high temperature [74][75][76][77][78][79]. Zhang et al demonstrated that mesoporous structure of SBA-15 can prevent sintering of monometallic Ni particles by confining their size inside the pores [74].…”
Section: Enhancement Of Dispersion and Thermal Stability Of Ni Nanopamentioning
confidence: 99%
“…Zhang et al demonstrated that mesoporous structure of SBA-15 can prevent sintering of monometallic Ni particles by confining their size inside the pores [74].…”
Section: Enhancement Of Dispersion and Thermal Stability Of Ni Nanopamentioning
confidence: 99%